SYNTHESIS, CHARACTERIZATION AND JUDD-OFELT ANALYSIS OF Eu(III) OR Sm(III) β-DIKETONATE COMPLEXES. - Scapolan, Maria I. X. (2021)
The lanthanide complexes [Ln(bmdm)3(L)] where Ln(III) = Eu and Sm were synthesized successfully using the diketone (1-(4-methoxyphenyl)-3-(4-tert-butylphenyl) propane-1,3-dione) (bmdm) and (L) = 1,10-phenanthroline (phen), 2,2'-bipyridine (bipy) ligands. The coordination modes were determined as bidentate chelate by the FT-IR. The ground state geometry was determined using the Sparkle/AM1 implemented in MOPAC2016 package. Europium complexes exhibit the characteristic emission bands that arise from 5D0→7FJ(J = 0-4); the presence of just one 5D0→7F0line transition means that this site is without the center of inversion. Samarium complexes display transitions at 4D5/2→6HJ(J = 5/2; 7/2; 9/2 and 11/2), being the 4D5/2→6H9/2the most intense, indicating that the forced electric dipole mechanism is predominant when compared with the magnetic dipole ones. The intensity parameters Ω2and Ω4were calculated according to the emission spectra for Eu(III) and absorption spectra for Sm(III). The high Ω2values demonstrated that the lanthanide ion in bipy or phen complexes is in a highly polarizable chemical environment. The emission lifetime (τ) increases compared with that of precursor aquo complexes, confirming that the non-radiative quenching is minimized. The low quantum efficiency is a result of NIR emissions and non-radiative transitions of Sm(III).